Nationwide collaborative development of learning outcomes and exemplar standards for Australian pharmacy programmes - Stupans, I.; McAllister, S.; Clifford, R.; Hughes, Jeff; Krass, I.; March, G.; Owen, S.; Woulfe, J. (Wiley-Blackwell Publishing Ltd, 2015)
Objectives Internationally, the preparation of pharmacy graduates for professional practice has evolved from educating for capacities for practice, to a focus on competencies, and most recently, on assuring graduate outcomes. Consequently, there is an increasing emphasis on the specification of and accountability around student learning outcomes. This, in turn, has implications for teaching and assessment. The aim of the study was to harmonise the various expectations and regulatory requirements for Australian pharmacy education programmes through the development of learning outcomes and exemplar standards for all entry-level pharmacy graduates. Methods Learning outcomes and exemplar standards were developed through a participatory action research framework which involved academic staff representatives from pharmacy schools in Australia, pharmacy student representatives, and the Australian Pharmacy Council (APC, the accreditation body for Australian pharmacy programs) involving an iterative process of dissemination and seeking of feedback. Key findings The key result from the project was the formulation of national pharmacy learning outcomes and exemplar standards (PhLOS) for all students graduating from entry-level pharmacy programmes. These have been endorsed by both students and academics. Conclusions Learning outcomes have been developed through a collaborative process for pharmacy programmes across Australia through harmonisation of the various expectations and regulatory requirements for pharmacy education programmes. Application of these learning outcomes and exemplar standards will ensure that all graduates of all entry-level pharmacy programmes will have achieved at least the same threshold, regardless of the university from which they graduate prior to entering their internship year.